Admit One : Writing Your Way into the Best Colleges - Richards, Thomas, 1956- (Book collections on Project MUSE., 2019)
"This books is a how-to guide that advises college applicants on how to craft an effective personal essay and an overall compelling, competent persona in their college applications by writing well. The goal is to help applicants gain admission to colleges of their choice by advising them on writing skills, with chapters on skills such as voice, diction, paragraph organization, narrative arc, etc. The book is aimed at high school junior and seniors, their parents, and their guidance counselors"--